2000
DOI: 10.1128/jvi.74.18.8434-8443.2000
|View full text |Cite
|
Sign up to set email alerts
|

Natural Genetic Exchanges between Vaccine and Wild Poliovirus Strains in Humans

Abstract: In a previous study of poliovirus vaccine-derived strains isolated from patients with vaccine-associated paralytic poliomyelitis (VAPP) (9, 11), we reported that a high proportion (over 50%) of viruses had a recombinant genome. Most were intertypic vaccine/vaccine recombinants. However, some had restriction fragment length polymorphism (RFLP) profiles different from those of poliovirus vaccine strains. We demonstrate here that five such recombinants, of 88 VAPP strains examined, carried sequences of wild (nonv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
168
1
10

Year Published

2001
2001
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(181 citation statements)
references
References 31 publications
2
168
1
10
Order By: Relevance
“…And fourth, since the rDEN4⌬30 vector is common to all the chimeric viruses of the tetravalent formulation, recombination between the vaccine serotypes would not lead to loss of the attenuating mutation or reversion to a wt phenotype. Recombination between components of the trivalent polio vaccine has been observed, 42 and naturally occurring recombinant dengue viruses have been described. 43 In summary, the DEN-4 vaccine candidate virus 2A⌬30 was well tolerated and induced an acceptable neutralizing antibody response in each of the 20 volunteers in this initial Phase I clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…And fourth, since the rDEN4⌬30 vector is common to all the chimeric viruses of the tetravalent formulation, recombination between the vaccine serotypes would not lead to loss of the attenuating mutation or reversion to a wt phenotype. Recombination between components of the trivalent polio vaccine has been observed, 42 and naturally occurring recombinant dengue viruses have been described. 43 In summary, the DEN-4 vaccine candidate virus 2A⌬30 was well tolerated and induced an acceptable neutralizing antibody response in each of the 20 volunteers in this initial Phase I clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…Serotypes 1, 2 and 3 of wild-type PVs have been reported to recombine with each other (Dahourou et al, 2002;Furione et al, 1993). Wild-type and OPV strains have been reported to recombine (Dahourou et al, 2002;Georgescu et al, 1995;Guillot et al, 2000;Liu et al, 2000Liu et al, , 2003Yang et al, 2003) and PVs have been shown to recombine with serotypes of HEV-C (Brown et al, 2003;Jiang et al, 2007;Rousset et al, 2003). Furthermore, vaccine-derived PV strains, defined as having more than 1 % nucleotide differences in the VP1 protein coding region (reviewed recently by Agol, 2006;Kew et al, 2004), have been reported to have an interserotypic recombinant genome (Blomqvist et al, , 2004Martin et al, 2002) as well as a recombinant genome with a non-structural region from an unknown HEV-C strain (Arita et al, 2005;Kew et al, 2002Kew et al, , 2004Rakoto-Andrianarivelo et al, 2008;Rousset et al, 2003;Shimizu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A high mutation rate is considered to be a major factor behind its genetic diversity (Simmonds, 1999(Simmonds, , 2001Farci & Purcell, 2000). Recombination provides another mechanism for creating genetic variation and is known to be widespread among nonsegmented RNA viruses, including other members of Flaviviridae (Lai, 1992;Figlerowicz et al, 1997;Worobey et al, 1999;Guillot et al, 2000;Twiddy & Holmes, 2003). Some viruses, such as coronaviruses, bromoviruses and carmoviruses, for example turnip crinkle virus (TCV), may undergo both homologous and non-homologous recombination, while some non-segmented plus-strand RNA viruses, such as picornaviruses, may only undergo homologous recombination (Lai, 1992).…”
mentioning
confidence: 99%